Middlemarch in the twenty-first century - Chase, Karen, 1952- (OUP E-Books., 2006)
"Middlemarch" is the prime example of George Eliot's dictum that "interpretations are illimitable," and in this collection of new essays, "Middlemarch" is re-examined as an open text responsive to gaps and fissures, and as resistant to authority as it is to other fixed notions of identity, idealism, and gender. What does the novel omit, and how do the omissions shape what is there? How shall we understand the materiality of the text? What problems does it pose to adaptation? The novel's plasticity becomes a basis for investigation into the multiple forms of expressiveness, and a consideration of how we might plot the patterns linguistically, ideologically, even cinematically. New spaces emerge within character, place, and narrative; what seemed absent or inaccessible assumes shape and definition; "Middlemarch" remains "Victorian" but it is a Victorianism understood through the dual perspectives of the 19th and 21st centuries. Scholars of George Eliot and students of Victorianism will be engaged by the wide-ranging scope of these essays, which nonetheless build on each other to form a coherent narrative of critical reflections.; If there is something for everyone in "Middlemarch", there is also something compelling about each of the essays in this collection